READING, LISTENING, WRITING AND ADVANTAGES OF SPEAKING - Xudayberganov Sherali Alisher o’g’li (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
In this article, the advantages of reading, listening, writing and speaking in learning foreign languages, as well as the fact that they develop students' cognitive activity, arouse interest in learning a foreign language and form communicative competence, were considered.